Key Determinants of Purchase Decision: A Case Study of Poeniko Batik Store in Pekalongan - Fatimah, Nurul; Prihandono, Dorojatun (Management Analysis Journal, 2020)
Business competition that is getting stonger makes SME (Small Medium Enterprise) must be able to compete. Batik is one of SME that has influence in economic growth. The enterpreneurs have to compete with competitiors. This study aims to examine the influence of media sosial, electronic word of mouth, and brand image on purchase decision through purchase intention at Poeniko Batik Pekalongan store. The population in this study is consumers of Poeniko Batik Pekalongan. The number of samples used in this study were 100 people using the incidental sampling method. The data collection method uses documentation and questionnaires. The results showed that the electronic word of mouth, brand image and purchase variables had a positive and significant effect on purchasing decisions. While social media variables do not have a positive and significant effect on purchasing decisions. The results of the path analysis test indicate that purchase intention can mediate the influence of social media, electronic word of mouth, and brand image on purchasing decisions.